Inaccuracies in Paper-Based Medical Record Information: An Exploratory Qualitative Case Study at Putri Hijau Hospital - Arie Widiansyah Hasibuan; Myrnawati Crie Handini; Asima Sirait; Donal Nababan; Kesaktian Manurung (PT Inovasi Pratama Internasional, 2026)
Paper-based medical records are vulnerable to incomplete, delayed, and inconsistent information, which may hinder data use in care delivery. This study explored medical record information inaccuracies, perceived contributing factors, perceived impacts, and prevention efforts at Rumah Sakit Tk II 01.05.01 Putri Hijau Kesdam I/BB Medan, in 2018. An exploratory qualitative case study used in-depth interviews with four purposively selected informants: a specialist physician, an inpatient ward nurse, a medical records officer, and an inpatient ward general practitioner. Each informant participated in one interview session, totaling 211 minutes. Transcripts were analyzed thematically; analytical decisions were traceable through an audit trail, member checking, and comparison of cross-professional perspectives. Analysis generated 13 substantive codes grouped into four themes. Documentation supported routine care but was not consistently complete or timely. Inaccuracies were perceived to relate to documentation awareness, workflow, service workload, and record verification; they could potentially disrupt continuity of clinical information, administrative processes, data functions, and quality. Prevention requires standard operating procedures, standardized formats, checklists, evaluation, feedback, and cross-professional accountability. The findings offer lessons for improving paper-based documentation and electronic medical record governance during digital transformation, without estimating the prevalence of inaccuracies or overall hospital quality in the single institutional case examined here.